2012
DOI: 10.1103/physrevb.85.014204
|View full text |Cite
|
Sign up to set email alerts
|

Atomic ordering in Au-(42 to 50) at.%Pd: A diffuse scattering and first-principles investigation

Abstract: Atomic ordering in Au-Pd alloys was studied by diffuse x-ray scattering and first-principles methods. Diffuse scattering was done of a single crystal of Au-48 at.% Pd that was aged at 703 K for 24 days. The weakly modulated short-range-order scattering exhibits diffuse maxima with an incommensurate wave vector, which can be related to a Fermi-surface nesting mechanism. From effective pair interaction parameters determined by the inverse Monte Carlo method, a one-dimensional long-period superstructure of the CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Also, the access to the distant coordination shells is necessary to discriminate between different alloying motifs. For example, a weak ordering of Pd and Au atoms was observed in thin films of PdAu and experimental and theoretical studies reported the formation of various superstructures in bulk PdAu. , Moreover, theoretical studies of configurations of Pd atoms on bimetallic surfaces indicate that configurations consisting of first-neighbor Pd pairs are unstable, but that the formation of second-neighbor Pd ensembles is energetically favorable. , The presence of such structural motifs can clearly have an impact on the catalytic properties of bimetallic NPs, and tools are needed to detect them in experiment.…”
Section: Exafs Modeling In Multielement Materialsmentioning
confidence: 99%
“…Also, the access to the distant coordination shells is necessary to discriminate between different alloying motifs. For example, a weak ordering of Pd and Au atoms was observed in thin films of PdAu and experimental and theoretical studies reported the formation of various superstructures in bulk PdAu. , Moreover, theoretical studies of configurations of Pd atoms on bimetallic surfaces indicate that configurations consisting of first-neighbor Pd pairs are unstable, but that the formation of second-neighbor Pd ensembles is energetically favorable. , The presence of such structural motifs can clearly have an impact on the catalytic properties of bimetallic NPs, and tools are needed to detect them in experiment.…”
Section: Exafs Modeling In Multielement Materialsmentioning
confidence: 99%
“…As in other substitutional solid solutions [7][8][9], the chemical interactions on the first CS are most essen tial; on the following CSs, they are less by approxi mately an order of magnitude and exhibit an alternat ing character.…”
Section: Chemical and Deformational Interactions In The Solid Solutiomentioning
confidence: 81%
“…In contrast to the chemical interactions, the defor mational interactions on the first CS are small; they are less by approximately two orders of magnitude than the deformational interactions for the first CS in the Au-Pd system [9]. On the other CSs, they are also substantially less, since the atoms of Au and Ag are close in size.…”
Section: Chemical and Deformational Interactions In The Solid Solutiomentioning
confidence: 84%
See 2 more Smart Citations